Does the Use of Videos in Flipped Classrooms in Engineering Labs Improve Student Performance? - Beatriz Del Río-Gamero; Dunia E. Santiago; Julieta Schallenberg-Rodríguez; Noemi Melián-Martel (Education Sciences, 2022)
This article analyzes whether the use of videos in flipped classrooms applied to lab practices in higher-education degrees improves the students’ performance. For this purpose, the flipped classroom methodology was used in the Sustainability and Environment Technologies subject, which is included in the curriculum of different engineering degrees. The results were evaluated by considering three different aspects: student satisfaction, student performance during the lab practice, and academic marks. The methodology of the study combines qualitative and quantitative approaches. The results show an improvement in student satisfaction, as well as in student performance during the lab practice. The academic marks of the test students in comparison to the control students also show some improvement. Overall, those who undertook the flipped classroom lab practice noted many benefits, including increased student engagement and satisfaction, as well as improvements in student skills and academic results. Novel aspects such as the qualitative and quantitative evaluations of the performance of the lab practice have been introduced in this research.